Penelitian terhadap Tingkat Stress yang Dialami oleh Pembelajar Bahasa Asing - Emi, Kawasaki (Bina Nusantara University, 2010)
Article reveals the difference of stress among students and lecturers when they were studying in the class. However, I focused this research only in the second language class. The distinction of the stress will be shown on graphic. I used questionnaire to collect the data from the students and lecturers that I had mentioned above.